Testing the effects of fabrication parameters on the post-fabrication shape change of a three-dimensional printed textile platform. Issue 17 (September 2021) - Khan, Zahangir; He, Han; Chen, Xiaochen; Sydänheimo, Lauri; Ukkonen, Leena; Virkki, Johanna
In this study, a moisture-stimulated three-dimensional printing filament was printed onto an elastic band. The created textile platform changes its shape permanently after exposure to a high-moisture environment. Three main manufacturing parameters – that is, the printed pattern's infill percentage, the printed pattern's thickness, and the textile stretch – were tested to study their effects on the platform curving process. It was observed that an increase of the printed pattern's infill density from 20% to 80%, or the printed pattern's thickness from 1.3 to 1.7 mm, resulted in reduced curvature, whereas an increase in the elastic band's stretch extent from 120% to 130% of its original length increased the curvature. The achieved results can be very useful in the design and development of future four-dimensional printed structures, as well as in optimizing and programming moisture sensor performance, as several sensor manufacturing parameters can be modified according to the application and use environment.